Patients’ Trajectory With Lung Cancer From Treatment Initiation to End-Of-Life: A Retrospective Cohort Study Using Claims Data in Japan - Yuri Ogura MD; Masahiro Iwasaku MD, PhD; Mami Ishida MD, PhD; Yuki Katayama MD, PhD; Naoya Nishioka MD, PhD; Kenji Morimoto MD, PhD; Chie Yamamoto MD; Shinsaku Tokuda MD, PhD; Yoshiko Kaneko MD, PhD; Tadaaki Yamada MD, PhD; Hideya Yamazaki MD, PhD; Masayoshi Inoue MD, PhD; et al. (Cancer Control)
Introduction This study aimed to describe the course of patients with lung cancer from treatment initiation to end-of-life. Methods This retrospective cohort study used Claims Data from the National Health Insurance and Advanced Elderly Medical Service System. We analyzed data from patients newly diagnosed with lung cancer between April 2013 and March 2021 who had been hospitalized at our University Hospital in urban area. We evaluated (1) treatment courses of these patients, and (2) end-of-life care and clinical factors related to end-of-life care. Results A total of 818 patients who were diagnosed with lung cancer and received lung cancer treatment were included, of whom 200 were assessed for end-of-life. During the study period, 464 patients underwent surgery, while 308 received chemotherapy without undergoing surgery. The patients generally received lung cancer treatment within 2 years. The median time from initial treatment to death was 13 months for deceased patients. Patients in the palliative care unit (PCU) constituted 9% at 30 days before death, 25% at 7 days before death, and 40.5% on the day of death, whereas only 15% died at home. The prevalence of end-of-life care in the home/PCU was elevated among patients receiving molecular targeted drugs and in the female group. Conclusion This study highlighted the patterns of end-of-life care following lung cancer treatment by using Claims Data. PCU utilization was concentrated in the period shortly before death, with fewer patients passing away at home. End-of-life care may be influenced by clinical factors, including the type of lung cancer treatment received, which may change the place of care.